2014
DOI: 10.1053/j.gastro.2014.01.046
|View full text |Cite
|
Sign up to set email alerts
|

Fascin Is Regulated by Slug, Promotes Progression of Pancreatic Cancer in Mice, and Is Associated With Patient Outcomes

Abstract: Background & AimsPancreatic ductal adenocarcinoma (PDAC) is often lethal because it is highly invasive and metastasizes rapidly. The actin-bundling protein fascin has been identified as a biomarker of invasive and advanced PDAC and regulates cell migration and invasion in vitro. We investigated fascin expression and its role in PDAC progression in mice.MethodsWe used KRasG12D p53R172H Pdx1-Cre (KPC) mice to investigate the effects of fascin deficiency on development of pancreatic intraepithelial neoplasia (Pan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
124
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 105 publications
(130 citation statements)
references
References 44 publications
(55 reference statements)
6
124
0
Order By: Relevance
“…Associations of binding specificity of Slug with these Ebox elements of CDH1 and Slug promoters were also affirmed using qPCR ( Figure 5A,5B). Thus, cell-free EMSA as well as synthetic ChIP-PCR assays affirmed similar, specific interactions of Slug with E-boxes in the CDH1 and Slug promoters like other members of the Snail family [28][29][30][31][32][33], with Slug displaying a moderate to strong affinity for 5"-CACCTG-3", weak affinity for 5"-CAGGTG-3" and none for 5"-CAGCTG-3" sequences [34,35]. Taken together, these results suggest possible auto-regulation of Slug.…”
Section: Accepted Manuscriptmentioning
confidence: 63%
“…Associations of binding specificity of Slug with these Ebox elements of CDH1 and Slug promoters were also affirmed using qPCR ( Figure 5A,5B). Thus, cell-free EMSA as well as synthetic ChIP-PCR assays affirmed similar, specific interactions of Slug with E-boxes in the CDH1 and Slug promoters like other members of the Snail family [28][29][30][31][32][33], with Slug displaying a moderate to strong affinity for 5"-CACCTG-3", weak affinity for 5"-CAGGTG-3" and none for 5"-CAGCTG-3" sequences [34,35]. Taken together, these results suggest possible auto-regulation of Slug.…”
Section: Accepted Manuscriptmentioning
confidence: 63%
“…Li et al [24] showed Facin-1 presence of in 95% of pancreatic ductal adenocarcinoma cells. In this study, the high histoscore significantly correlated with a lower patients' survival rate, invasion to blood and lymphatic vessels and advanced staging of cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The overexpression of fascin has been reported in almost all the carcinomas (2,14,26,27), and fascin overexpression uniformly correlates with aggressive clinical course, metastatic progression, and poor prognosis (14, 28 -33). The transcriptional regulation of fascin in cancer has been extensively studied, with inflammatory cytokines, hypoxia, epithelial to mesenchymal transcription factors, and Wnt/␤-catenin pathways, among others, being implicated in the up-regulation of fascin levels in various cancers (33)(34)(35)(36)(37)(38). In contrast, little is known about the post-translational regulation of fascin other than the Ser 39 phosphorylation by PKC.…”
Section: Discussionmentioning
confidence: 99%